Brassicaceae microgreens: A novel and promissory source of sustainable bioactive compounds - Alloggia, Florencia Pía (2023)
Microgreens are novel foods with high concentrations of bioactive compounds and can be grown easily and sustainably. Among all the microgreens genera produced, Brassicaceae stand out because of the wide evidence about their beneficial effects on human health attributed to phenolic compounds, vitamins, and particularly glucosinolates and their breakdown products, isothiocyanates and indoles. The phytochemical profile of each species is affected by the growing conditions in a different manner. The agronomic practices that involve these factors can be used as tools to modulate and enhance the concentration of certain compounds of interest. In this sense, the present review summarizes the impact of substrates, artificial lighting, and fertilization on bioactive compound profiles among species. Since Brassicaceae microgreens, rich in bioactive compounds, can be considered functional foods, we also included a discussion about the health benefits associated with microgreens’ consumption reported in the literature, as well as their bioaccessibility and human absorption. Therefore, the present review aimed to analyze and systematize cultivation conditions of microgreens, in terms of their effects on phytochemical profiles, to provide possible strategies to enhance the functionality and health benefits of Brassicaceae microgreens.